KAJIAN PEMBUATAN PERMEN JELLY NANAS (Ananas comosus (L) Merr): PERBANDINGAN BAGIAN BUAH NANAS - Sandytia Permata Sari; Yohana Sutiknyawati Kusuma Dewi; Oke Anandika Lestari (Jurnal Sains Pertanian Equator, 2019)
ABSTRACT        Diversification of jelly-candy will be developed by pineaple flesh and core. the study of a pineapple jelly-candy (ananas comosus (l) merr): with different part of fruIt have find. The addition of pineapple core extract in the making of jelly-candy is a new breakthrough that makes jelly-candy more economical. The goal of this research was to find out of the best formulation of part of pineaple fruit best on physicochemical characterized and sensory evaluation. This research used randomized block design (RBD) of one factor, namely the proportion of flesh and core (f), consist of 5 levels are f(1): 100 % flesh; (f2):100 % core: f(3): 50 % flesh:50 % core; f(4): 25 % core:75 % flesh and f(5): 25 % flesh: 75 % core with 5 replications. The results showed that pineapple jelly candy-was produced by 100 % of core is the best formulation basev on physicochemical and sensory characterized. The physicochemical of pineapple jelly-candy were moisture content (12.40 %), ash content (0.46 %), Total Soluble Solid Solid  (27.14 °Brix), total acidity (0.06 %), Vitamin C (14.77 mg/100g), level of hardness (0.09 kgf). The best sensory characteristics were texture (3.8), the flavor of (3.20), aroma of (3.13), the color of (3.87), and preference 0f (3.63). The value of formulation De Garmo was (0.60).Keywords : core, flesh, pineapple, jelly-candy